Magnetic trapping on an atom chip - Bartoszek-Bober, Dobrosława; Panaś, Roman; Kawalec, Tomasz (Photonics Letters of Poland, 2013)
The article reviews briefly the rapidly evolving field of so-called atom chips for neutral atoms. Emphasis is placed on magnetic microtraps – on-chip Ioffe-Prichard and dimple trap issue is covered in some detail. The experimental setup for cooling and trapping 87Rb atoms is also presented together with some early results of on-chip magnetic trapping. Full Text: PDF References J. Schmiedmayer, "Guiding and trapping a neutral atom on a wire", Phys. Rev. A 52, R13 (1995). CrossRef M. H. Anderson, J. R. Ensher, M. R. Matthews, C. E. Wieman, and E. A. Cornell, "Observation of Bose-Einstein Condensation in a Dilute Atomic Vapor", Science 269, 198 (1995). CrossRef K. B. Davis, M.-O. Mewes, M. R. Andrews, N. J. van Druten, D. S. Durfee, D. M. Kurn et al., "Bose-Einstein Condensation in a Gas of Sodium Atoms", Phys. Rev. Lett. 75, 3969 (1995). CrossRef J. D. Weinstein, K. G. Libbrecht, "Microscopic magnetic traps for neutral atoms", Phys. Rev. A 52, 4004 (1995). CrossRef D. Müller, D. Z. Anderson, R. J. Grow, P. D. D. Schwindt, and E. A. Cornell, "Guiding Neutral Atoms Around Curves with Lithographically Patterned Current-Carrying Wires", Phys. Rev. Lett. 83, 5194 (1999). CrossRef N. H. Dekker, C. S. Lee, V. Lorent, J. H. Thywissen, S. P. Smith, M. Drndi et al., "Guiding Neutral Atoms on a Chip", Phys. Rev. Lett. 84, 1124 (2000). CrossRef J. Reichel, W. Hänsel, and T. W. Hänsch, "Atomic Micromanipulation with Magnetic Surface Traps", Phys. Rev. Lett. 83, 3398 (1999). CrossRef D. Cassettari, B. Hessmo, R. Folman, T. Maier, and J. Schmiedmayer, "Beam Splitter for Guided Atoms", Phys. Rev. Lett. 85, 5483 (2000). CrossRef M. A. Cirone, A. Negretti, T. Calarco, P. Krüger, J. Schmiedmayer, "A simple quantum gate with atom chips", Eur. Phys. J. D 35, 165 (2005). CrossRef W. Hänsel, P. Hommelhoff, T. W. Hänsch, and J. Reichel, "Bose–Einstein condensation on a microelectronic chip", Nature 413, 498 (2001). CrossRef H. Ott, J. Fortagh, G. Schlotterbeck, A. Grossmann, and C. Zimmermann, "Bose-Einstein Condensation in a Surface Microtrap", Phys. Rev. Lett. 87, 230401 (2001). CrossRef Y. Lin, I. Teper, C. Chin, V. Vuletić, "Impact of the Casimir-Polder Potential and Johnson Noise on Bose-Einstein Condensate Stability Near Surfaces", Phys. Rev. Lett. 92, 050404 (2004). CrossRef E. Salim, J. DeNatale, D. Farkas, K. Hudek, S. McBride, J. Michalchuk et al, "Compact, microchip-based systems for practical applications of ultracold atoms", Quantum Inf. Process. 10, 975 (2011). CrossRef S. Groth, Development, "Fabrication and Characterisation of Atom Chips", doctoral dissertation. (2006). R. Folman, P. Krüger, J. Schmiedmayer, J. Denschlag, C. Henkel, "Microscopic atom optics: From wires to an atom chip", Adv. At. Mol. Opt. Phys. 48, 263 (2002). CrossRef A. Arnold, Preparation and Manipulation of an 87Rb Bose-Einstein Condensate (University of Sussex 1999), PhD thesis. D. M. Farkas, K. M. Hudek, E. A. Salim, S. R. Segal, M. B. Squires, and D. Z. Anderson, "A compact, transportable, microchip-based system for high repetition rate production of Bose–Einstein condensates ", Appl. Phys. Lett. 96, 093102 (2010). CrossRef K. Dieckmann, R. J. C. Spreeuw, M. Weidemüller, and J. T. M. Walraven, "Two-dimensional magneto-optical trap as a source of slow atoms", Phys. Rev. A 58, 3891 (1998). CrossRef W. Petrich, M. H. Anderson, J. R. Ensher, and E. A. Cornell, "Behavior of atoms in a compressed magneto-optical trap", J. Opt. Soc. Am. B, 11, 1332 (1994). CrossRef